Chapter Les monnaies alternatives à Rouen à la fin du Moyen Âge - Kucab, Anne (Firenze University Press, 2025)
Sources from Rouen from the second half of the 15th century provide information on economic transactions in one of the major cities in the kingdom of France. Thanks to the accounting records, it is possible to determine the significant role played by alternative currencies in the lives of the inhabitants. Alternative currencies took several forms: barter, payroll deductions and payments in kind. They are used in a variety of transactions: in the context of work, commercial exchanges, as a reward for workers or as a gift for prominent people. Both their practical and symbolic dimensions need to be taken into account. Their use underlines the Rouen people's ability to combine real money, account money and payment in kind.